Pemanfaatan Bubuk Kedelai dan Ekstrak Kulit Buah Naga sebagai MP-ASI Padat Gizi: Pemanfaatan Bubuk Kedelai dan Ekstrak Kulit Buah Naga sebagai MP-ASI Padat Gizi - Arinda Lironika Suryana; Nita Maria Rosiana; Zora Olivia (Universitas Airlangga, 2022)
Background: Complementary feeding is given to infant aged 6-24 months. Complementary feeding can be made from several food ingredients to get products with high nutritional value. Complementary feeding product development should meet the Indonesian National Standard for Instant Powder (01-7111.1-2005). Objectives: The purpose of this study was to determine effect of ingredient formulation on the nutritional content of complementary food and to compare with complementary feeding standard. Methods: The research treatment was ratio of soy powder and milk powder (1:1; 5:9; 9:5). The ingredients used were soybean powder, milk powder, dragon fruit peel extract and sugar. The research design used completely randomized design (CRD). Complementary feeding nutrient analysis includes proximate analysis, vitamins and minerals. Data analysis used was ANOVA. Results: Complementary feeding contains 2.35-2.91% of water content, 4.17-5.92% of ash content, 15.09-15.18% of fat, 15.84-20.05% of protein, 57.04-62.48 carbohydrate, 9.51-14.49% of dietary fiber, 444.123-449.85kcal/100g of energy, 27.16-34.35mg/100g of vitamin C, 181.23-267.63mg/100g of calcium, 13.93-37.66mg/100g of iron, 7.11-10.47mg/100g of zinc, and 149.93-185.80mg/100kcal of sodium and. Water content, protein, sugar, energy, vitamin C, iron are in accordance with complementary feeding standard. Conclusions: The formulation of the ratio of soy powder and milk powder gives significant effect to ash content, protein =, carbohydrates, dietary fiber and iron content of developed complementary feeding. However, the formulation did not results a significant effect to the fat, energy, calcium, zinc and sodium levels of complementary feeding. It is necessary to reduce dietary fiber and ash content in order to fulfill complementary feeding standards.